Analysis of genetic divergence in menthol mint (Mentha arvensis L.) - H P Singh, S P Singh, A K Singh, (Journal of Spices and Aromatic Crops, 2017)
Sixteen genotypes of menthol mint (Mentha arvensis) were evaluated for five quantitativetraits namely, plant height, number of internodes, length of internodes, leaf:stem ratio andoil content at Pantnagar (Uttaranchal). These genotypes were grouped into five clusters onthe basis of Mahalanobis D2 analysis. The characters namely, length of internode and num-ber of internodes had maximum contribution towards genetic divergence. The mean perfor-mance of the genotypes in each cluster and their D2 values revealed that genotypes can beselected to obtain superior half-sib progenies.